PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING BERORIENTASI KONSEP TRI HITA KARANA UNTUK MENINGKATKAN HASIL BELAJAR IPAS - I Komang Muliantara ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2022)
This study aims to improve student learning outcomes in class IV. This research is a classroom action research. Based on the results of initial observations, student learning outcomes are still low. This study uses the Tri Hita Karana oriented Creative Problem Solving learning model. This research was conducted at SD Negeri 4 Bebetin in class IV students with a total of 26 students, consisting of 9 male students and 17 female students. Based on the research results, there was an increase in class average scores and the percentage of student learning completeness from cycle I to cycle II. In cycle I, the average value was 72.12. The percentage of learning completeness of 72.12% is in the criteria of sufficient completion. The average value in cycle II increased to 80.19. The percentage of learning completeness reached 80.19% in the complete criteria. The results in cycle II have met the research success indicators that have been set at â‰¥ 75%. This it can be said that the application of the Tri Hita Karana-oriented Creative Problem Solving learning model can improve the science learning outcomes of class IV students at SD Negeri 4 Bebetin semester I of the 2022/2023 academic year.